2012
DOI: 10.1155/2012/752820
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing Does Not Have to Be Sedentary: Motivation to Participate in a TV Exercise Program

Abstract: The present study explored which underlying motivations induced people to participate in a television exercise program called “The Netherlands on the Move!-television” (NOM-tv). A cross-sectional study was carried out among 1,349 viewers of NOM-tv. The respondents completed the intrinsic motivation inventory (IMI), assessing their levels of intrinsic motivation towards participating in the NOM-tv exercises. The results showed that higher levels of intrinsic motivation (i.e. enjoying the NOM-tv exercises, feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Average daily in-game steps between 1619 and 2206 throughout the intervention period indicate a substantially better PA adherence that is especially meaningful when considering the distinctly longer timeframe of 24 weeks. The stable, objectively measured increases in weekly PA during the intervention period, along with the positive association between total in-game training (minutes) and change in IMI score, further confirm the previously indicated [25,36] importance of pursuing improvements in intrinsic motivation through increased PA enjoyment especially in behavioral interventions targeting inactive and unmotivated individuals. As this smartphone game is a motivating and enjoyable experience, the subjectively perceived cost of PA is reduced and people are encouraged to engage in regular PA based on their personal intrinsic motivation [14,43].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Average daily in-game steps between 1619 and 2206 throughout the intervention period indicate a substantially better PA adherence that is especially meaningful when considering the distinctly longer timeframe of 24 weeks. The stable, objectively measured increases in weekly PA during the intervention period, along with the positive association between total in-game training (minutes) and change in IMI score, further confirm the previously indicated [25,36] importance of pursuing improvements in intrinsic motivation through increased PA enjoyment especially in behavioral interventions targeting inactive and unmotivated individuals. As this smartphone game is a motivating and enjoyable experience, the subjectively perceived cost of PA is reduced and people are encouraged to engage in regular PA based on their personal intrinsic motivation [14,43].…”
Section: Discussionsupporting
confidence: 83%
“…A comparison of the magnitude of these improvements with other studies is difficult, since no studies used IMI to assess changes in intrinsic motivation in game-based interventions that promote PA. However, a cross-sectional study [36] showed that enjoyment and perceived competence of performing a television exercise program (ie, higher intrinsic motivation) are the most predictive factors of more frequent participation in the program. The recorded in-game training data in our study support this finding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations